Cloudiness, the planetary radiation budget, and climate - Ellis, James S. (James Stephen), author; Vonder Haar, Thomas H., advisor; Cox, Stephen K., committee member (Colorado State University. Libraries, 1978)
Satellite planetary radiation budget measurements from the Nimbus 3 satellite for four semi-monthly periods along with a 29 month composite of measurements from six satellites are applied in a quantitative study to evaluate the effect of cloudiness on the planetary radiation budget. Annual and seasonal results are expressed as zonal, hemispherical and global mean values. The results show that for the planet as a whole the effect of "present day" clouds in reducing the absorbed shortwave flux is larger than their effect in reducing the long wave emitted flux. The difference between the two effects is significantly larger over oceans than over land. Similarly, the sensitivity to changes in cloud amount is greater in the shortwave absorbed flux than in the longwave flux emitted to space. It was also shown that the presence of clouds act to reduce the amplitude of the annual variation of the global planetary net radiation budget. One may hypothesize from the results of this study and the works of others that a uniform increase in global cloud amount (in the absence of changes in cloud top height, cloud albedo, other atmospheric constituents, and vertical temperature lapse rates) will decrease the global mean surface temperature until radiative equilibrium is restored.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Cloudiness; Energy budget (Geophysics); Terrestrial radiation; Solar radiation